2006
DOI: 10.1088/0741-3335/48/9/001
|View full text |Cite
|
Sign up to set email alerts
|

Inward thermodiffusive particle pinch in electron internal transport barriers in TCV

Abstract: Electron internal transport barriers (eITBs) are obtained in TCV with different heating and current drive schemes. They are sustained in steady-state conditions for several energy confinement and current redistribution times. In these scenarios, the density profile displays a different behaviour with respect to normal L-mode plasmas, with or without auxiliary heating. In fully noninductive discharges developing an eITB, the density profile shape is strongly correlated with the electron temperature profile, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
39
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 24 publications
1
39
1
Order By: Relevance
“…The former study, based on mixing length estimates, has shown that the stabilization of trapped electron modes (TEMs) by (s − α) effects provides an explanation for the reduced heat transport in the barriers. The latter study enabled us to show that the stabilization of TEMs can furthermore explain the significant electron thermo-diffusive pinch and resulting density peaking observed, albeit with strong central electron heating [6]. More specifically, the quasi-linear model presented in [11] has shown how the interplay of ion temperature gradient (ITG) and TEMs may lead to a zero electron particle flux for the correct combination (R/L n e , R/L T e , R/L T i ) of normalized electron density, electron temperature and ion temperature gradients, respectively.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…The former study, based on mixing length estimates, has shown that the stabilization of trapped electron modes (TEMs) by (s − α) effects provides an explanation for the reduced heat transport in the barriers. The latter study enabled us to show that the stabilization of TEMs can furthermore explain the significant electron thermo-diffusive pinch and resulting density peaking observed, albeit with strong central electron heating [6]. More specifically, the quasi-linear model presented in [11] has shown how the interplay of ion temperature gradient (ITG) and TEMs may lead to a zero electron particle flux for the correct combination (R/L n e , R/L T e , R/L T i ) of normalized electron density, electron temperature and ion temperature gradients, respectively.…”
Section: Introductionmentioning
confidence: 80%
“…Such electron barriers have been systematically obtained in TCV under conditions of low or negative magnetic shearŝ, leading simultaneously to sharp density and electron temperature gradients [3][4][5][6][7]. Although heating (in particular, electron cyclotron resonance heating, ECRH) is applied to the core of the plasma, no external particle fueling is provided to this central region in these discharges.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The density peaking in the C-Mod ITBs was thought to result from the Ware pinch, with the ITB density gradient during electron heating determined by the balance of Ware pinch and TEM turbulent fluxes, thus acquiring a strong inverse dependence on temperature. In TCV electron ITBs, where transport barriers are seen mainly on the electron temperature profile [5], the density peaking results from a strong thermodiffusive pinch [6] component which can be explained [3] using the quasi-linear model that shall be used in this paper .…”
Section: Introductionmentioning
confidence: 99%